Sensitive electrochemical detection of cardiac troponin I in serum and saliva by nitrogen-doped porous reduced graphene oxide electrode - Chekin, Fereshteh; Vasilescu, Alina; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Iancu, Madalina; Badea, Gabriela; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Cardiovascular diseases pose one of the highest mortality risks among all diseases in developed countries, steadily increasing the burden on the health systems. Early diagnosis of cardiovascular diseases has consequently become highly important to decrease mortality and to use more adapted therapeutic decisions. We demonstrate here the utility of nitrogen-doped reduced graphene oxide (N-prGO) for detecting and quantifying of cardiac troponin I (cTnI), a key human cardiac protein biomarker, under physiologically relevant conditions. Non-covalent modification of N-prGO by 1-pyrenecarboxylic acid (py-COOH) and poly(ethylene glycol) modified pyrene (py-PEG) ligands allowed the covalent integration of Tro4 aptamer, known for its high selectivity towards cTnI. Using differential pulse voltammetry (DPV), a label-free electrochemical sensor for cTnI for concentrations down to 1 pgmL(-1) in human serum could be obtained. This sensitive detection arises from the integration of a porous nanomaterial with excellent electrochemical properties being easily amendable to site-specific surface modification. (C) 2018 Elsevier B.V. All rights reserved.